Interaural Place-of-Stimulation Mismatch Estimates Using CT Scans and Binaural Perception, But Not Pitch, Are Consistent in Cochlear-Implant Users - Bernstein, Joshua G.W.; Jensen, Kenneth K.; Stakhovskaya, Olga A.; Noble, Jack H.; Hoa, Michael; Kim, H. Jeffery; Shih, Robert; Kolberg, Elizabeth; Cleary, Miranda; Goupell, Matthew J. (The Journal of neuroscience, 2021)
Bilateral cochlear implants (BI-CIs) or a CI for single-sided deafness (SSD-CI; one normally functioning acoustic ear) can partially restore spatial-hearing abilities, including sound localization and speech understanding in noise. For these populations, however, interaural place-of-stimulation mismatch can occur and thus diminish binaural sensitivity that relies on interaurally frequency-matched neurons. This study examined whether plasticity—reorganization of central neural pathways over time—can compensate for peripheral interaural place mismatch. We hypothesized differential plasticity across two systems: none for binaural processing but adaptation for pitch perception toward frequencies delivered by the specific electrodes. Interaural place mismatch was evaluated in 19 BI-CI and 23 SSD-CI human subjects (both sexes) using binaural processing (interaural-time-difference discrimination with simultaneous bilateral stimulation), pitch perception (pitch ranking for single electrodes or acoustic tones with sequential bilateral stimulation), and physical electrode-location estimates from computed-tomography (CT) scans. On average, CT scans revealed relatively little BI-CI interaural place mismatch (26° insertion-angle mismatch) but a relatively large SSD-CI mismatch, particularly at low frequencies (166° for an electrode tuned to 300 Hz, decreasing to 14° at 7000 Hz). For BI-CI subjects, the three metrics were in agreement because there was little mismatch. For SSD-CI subjects, binaural and CT measurements were in agreement, suggesting little binaural-system plasticity induced by mismatch. The pitch measurements disagreed with binaural and CT measurements, suggesting place-pitch plasticity or a procedural bias. These results suggest that reducing interaural place mismatch and potentially improving binaural processing by reprogramming the CI frequency allocation would be better done using CT-scan than pitch information. SIGNIFICANCE STATEMENT Electrode-array placement for cochlear implants (bionic prostheses that partially restore hearing) does not explicitly align neural representations of frequency information. The resulting interaural place-of-stimulation mismatch can diminish spatial-hearing abilities. In this study, adults with two cochlear implants showed reasonable interaural alignment, whereas those with one cochlear implant but normal hearing in the other ear often showed mismatch. In cases of mismatch, binaural sensitivity was best when the same cochlear locations were stimulated in both ears, suggesting that binaural brainstem pathways do not experience plasticity to compensate for mismatch. In contrast, interaurally pitch-matched electrodes deviated from cochlear-location estimates and did not optimize binaural sensitivity. Clinical correction of interaural place mismatch using binaural or computed-tomography (but not pitch) information may improve spatial-hearing benefits.